Applying Complexity Theory : Whole Systems Approaches to Criminal Justice and Social Work - Bartollas, Clemens; Pycroft, Aaron (Book collections on Project MUSE., 2014)
Approaches based around complexity theory are increasingly being used in the study of organisations and the delivery of services. This is the first book to explore the application of complexity theory to difficult practice issues in criminal justice and social work and is intended to stimulate debate. It brings together experts in this emerging field to address complexity theory from a range of perspectives (positivist, realist, and constructivist), providing a detailed but accessible discussion of the key issues to whole systems approaches.